Census of Population, 1880 (United States): Public Use Sample - Ruggles, Steven ([Verlag nicht ermittelbar], 1995)
This data collection provides the full 1880 Public Use Sample drawn from census enumeration forms. The file contains two types of records: household and person. Each household record is followed by a record for each person in the household. This collection contains information about size of family, number of persons and families in the dwelling, and the geographic location of each household. Information on individuals includes demographic characteristics such as age, sex, and marital status, as well as occupation, health, education, and nativity.